Utilization of Audio Visual Media "Tolak Handi" as an Effort to Prevent Child Marriage - Anjar Astuti; Yanik Muyassarah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Child marriage can have negative impacts on women, especially during pregnancy, childbirth, and postpartum. Lack of education regarding child marriage is a contributing factor to the high number of cases in Indonesia. Audio-visual media is an appropriate medium for providing education because it provides good visualization, facilitating the development of knowledge. The purpose of this study is to analyze the impact of the use of the audio-visual media "TOLAK HANDI" as an effort to prevent child marriage. This study uses quasi experimental research with a plan randomised perspective study, pre posttest control. The sample in this study were adolescents. Bivariate analysis used independent t-test. Results: From the results of statistical tests, it is known that there is a difference in adolescent knowledge about preventing child marriage in the control group and the treatment group with a p value of 0.000. There is a difference in adolescent attitudes about preventing child marriage in the control group and the treatment group with a p value < 0.000. Conclusion: There is an influence of the use of Audio Visual Media "TOLAK HANDI" on changes in adolescent knowledge and attitudes in preventing child marriage.